Effects of wastewater irrigation on soil physico-chemical properties and vegetables quality: A review - Sibanda, Justice; Parwada, Cosmas; Mvumi, Cluver (International Journal of Horticultural Science, 2025)
This study analyses the use of raw urban wastewater for irrigation and its effects on soil characteristics and heavy metal pollution within crops. There is rampant use of urban waste water by small scale urban vegetable farmers in Zimbabwe. This is posing health hazards to the consumers of urban vegetables and decrease in soil functioning. The significance of this study was to appraise the research study related to the use of urban waste water to answer the research question: What is the impact of waste water on selected soil physico-chemical properties and quantities of heavy metals in vegetables irrigated with waste water? A systematic review of 3100 articles from PubMed, Scopus, Web of Science, and Google Scholar (2010–2024) was performed within PRISMA guidelines. After excluding irrelevant studies, 49 from Nigeria, Bangladesh, Iran, Egypt, India, Pakistan, China, Saudi Arabia, and DRC were selected for analysis. These countries were found to have a lot of literature on urban waste water irrigation. This literature review identified an overview of existing literature on urban waste water irrigation and synthesise findings to provide a comprehensive overview of the topic  The results showed (P